In-Situ Characterization of Lithium Native Passivation Layer in A High Vacuum Scanning Electron Microscope. (August 2019) - Bessette, Stéphanie; Hovington, Pierre; Demers, Hendrix; Golozar, Maryam; Bouchard, Patrick; Gauvin, Raynald; Zaghib, Karim
Abstract: A technique to characterize the native passivation layer (NPL) on pure lithium metal foils in a scanning electron microscope (SEM) is described in this paper. Lithium is a very reactive metal, and consequently, observing and quantifying its properties in a SEM is often compromised by rapid oxidation. In this work, a pure lithium energy-dispersive x-ray spectrum is obtained for the first time in a high vacuum SEM using a cold stage/cold trap with liquid nitrogen reservoir outside the SEM chamber. A nanomanipulator (OmniProbe 400) inside the microscope combined with x-ray microanalysis and windowless energy dispersive spectrometer is used to fully characterize the NPL of lithium metal and some of its alloys by a mechanical removal procedure. The results show that the native films of pure lithium and its alloys are composed of a thin (25 nm) outer layer that is carbon-rich and an inner layer containing a significant amount of oxygen. Differences in thickness between laminated and extruded samples are observed and vary depending on the alloy composition.